Uma avaliação de impacto do regime de substituição tributária sobre arrecadação nas operações com brinquedos no Estado do Ceará – Dec. nº 31.638/14 - Magalhães, Roberto Wagner Ferreira Gomes (2017)
The state decree No. 31,638 of December 8, 2014 establishes in Ceará the regime of tax substitution aiming to foment in the sector of manufacture and commercialization of toys. This device aimed at simplifying the companies, providing more competitiveness to the segment of an estimate of industrialization and commercialization in the state. Thus, the present study evaluated the impact of the measure on an ICMS collection of the sector. To do so, it was used as a loss model in dozens of approval data, referring to the decree, with manufacturers and merchants of toys as treatment group and branches. The results are positive for an average reduction of 12.5 thousand reais in the taxpayer's income in the sector (22%), reduction of difficulty to more than 30 miles in the MEI and Microenterprises (55%). On the other hand, taxpayers of the Normal type, have their average collection of ICMS raised around 180 thousand reais (+14.4%). Thus, a policy seems to have been effective in discarding the sector, fostering its competitiveness in the state.